Utilization of residual space of deciduous second molar to align teeth in a crowded arch - Nessa, Kamrun; Anwar, Nabila; Ghosh, Ranjit; Mondal, Sonali; Alam, Mohammad Khursheed (Bangladesh Journal of Medical Science, 2020)
The decision forutilization of a space of a retained deciduous molar to alleviate crowding in late mixed dentition is one of the critical aspects in orthodontic treatment.Hence, the aimof the treatment hereis to use the extraction spaces properly to relieve severe crowding and align both the arches to the point where a stable overjet/overbite exist. This case report presenting a 13-year-old female adolescent with severe crowding in both upper and lower jaw and a convex profile. Although she was initially anxious to extract her teeth to treat her case but also she was looking for desirable results. The case was later treated in a conventional orthodontic approach with extraction ofthree 1stpremolars. It was quite challenging to make the best use of the space of missing lower right 2nd premolar after extraction of deciduous second molar on that sideto relieve severe crowding. However; at the end of the treatment, the patient expressed satisfaction with the results- proper bite, smile and most importantly esthetics. This case report demonstrates successful treatment of an adolescent patient with severe crowding by proper utilization of the extraction spaces. Bangladesh Journal of Medical Science Vol.19(4) 2020 p.763-768